Serum Uric Acid and Radiological Markers as Predictive Biomarkers in Psoriatic Arthritis Development - Sohail Awan, Noor-Ul-Ain Malik Sohail, Attka Maryam, Pehlaj Rai, Aisha Malik, Rahat Rahman, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Serum uric acid concentration and radiological features were assessed as prospective biomarkersfor the development of psoriatic arthritis in a cohort of psoriasis subjects. Prospectiveobservational study enrolled 180 adults with plaque psoriasis, including 60 who developedpsoriatic arthritis (PsA) at one-year follow-up versus